Enlarged adipocytes from subcutaneous vs. visceral adipose tissue differentially contribute to metabolic dysfunction and atherogenic risk of patients with obesity - Suárez-Cuenca, Juan Antonio; De La Peña-Sosa, Gustavo; De La Vega-Moreno, Karen; Banderas-Lares, Diana Zaineff; Salamanca-García, Moisés; Martínez-Hernández, José Enrique; Vera-Gómez, Eduardo; Hernández-Patricio, Alejandro; Zamora-Alemán, Carlos Ramiro; Domínguez-Pérez, Gabriela Alexandra; Ruíz-Hernández, Atzín Suá; Gutiérrez-Buendía, Juan Ariel; et al. (Scientific reports, 2021)
Morphological characteristics and source of adipose tissue as well as adipokines may increase cardiometabolic risk. This study aimed to explore whether adipose tissue characteristics may impact metabolic and atherogenic risks. Subcutaneous Adipose Tissue (SAT), Visceral Adipose Tissue (VAT) and peripheral blood were obtained from obese patients submitted to bariatric surgery. Adipose tissue (morphometry), plasma adiponectin, TNF-α, resistin (multiplexing) and biochemical chemistry were analyzed; as well as endothelial dysfunction (Flow Mediated Dilation, FMD) and atherogenesis (Carotid Intima Media Thickness, CIMT). Subgroups divided by adipocyte size and source were compared; as well as correlation and multivariate analysis. Sixty patients 36.6% males, aged 44 years-old, BMI 46.7 kg/m 2 were included. SAT’s adipocytes showed a lower range of size expandability than VAT’s adipocytes. Independent from their source, larger adipocytes were associated with higher glucose, lower adiponectin and higher CIMT. Particularly, larger adipocytes from SAT were associated with higher blood pressure, lower insulin and HDL-cholesterol; and showed positive correlation with glucose, Hb A1c , systolic/diastolic values, and negatively correlated with insulin and adiponectin. VAT’s larger adipocytes particularly associated with lower resistin and lower FMD values. Gender and Diabetes Mellitus significantly impacted the relation of adipocyte size/source with the metabolic and atherogenic risk. Multivariable analysis suggested hypertension-resistin-Hb A1c interactions associated with SAT’s larger adipocytes; whereas potential insulin-adiponectin associations were observed for VAT’s larger adipocytes. Adipocyte morphology and source are differentially related with cardiometabolic and atherogenic risk in population with obesity, which are potentially affected by gender and Diabetes Mellitus.